Exploration of Character Education Programs and Their Contribution to the Moral Formation of Junior High School Students - Sawaliyah, Yuniarsih; Azhar, Azhar (Program Pascasarjana, Universitas Islam Bunga Bangsa Cirebon, 2025)
This study aims to analyze the impact of character education programs on the moral formation of students in the junior high school environment. The context of this research arises from the growing concern about the decline of moral values among adolescents, which is reflected in issues such as indiscipline, lack of respect for teachers and peers, and weak sense of responsibility in the school environment. Character education is therefore seen as one of the strategic efforts in instilling moral values such as honesty, responsibility, and respect in students from an early age. The method used in this study is a qualitative approach with a case study in one of the junior high schools in Indonesia. Data collection techniques were conducted through observation, in-depth interviews with teachers and students, as well as documentation of character education activities. The results showed that the implementation of character education program has a positive impact on the moral behavior of students, especially in aspects of discipline, responsibility, and empathy for others. Learning that is integrated with character values, as well as support from the school environment and family, are key factors in the success of the program. However, there are still some challenges such as the lack of consistency in the implementation of the program and the limitations of teacher training in implementing a character-based approach. In conclusion, the character education program has a significant contribution in the formation of student morale, but its sustainability and effectiveness are highly dependent on the commitment of all components of the school as well as collaboration with parents. The recommendations of this study emphasize the importance of periodic evaluation, teacher training, and active involvement of all parties in building a school culture of character.